2012
DOI: 10.4021/jocmr775w
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Transformation of Portal Vein Secondary to Portal Vein Thrombosis: A Case Report

Abstract: There are few reported cases of cavernous transformation of the portal vein (CTPV) in adults. We present a case of a 58 year-old male who was found to have this complication due to portal vein thrombosis (PVT). A 58-year old African American male with chronic alcohol and tobacco use presented with a 25-day history of weakness, generalized malaise, nausea and vomiting associated with progressively worsening anorexia and weight loss. The patient was admitted for severe anemia in conjunction with abnormal liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…It is a phenomenon to help keep liver to retain its functioning in a normal way; however, if this cavernous formation is unable to handle mesenteric and splenic inflow, the formation of pre-sinusoidal portal hypertension or cirrhosis ensues. Obstruction of portal veins was first diagnosed in 1869 by Stewart and Balfour in a patient with variceal dilation, enlarged spleen and ascites [4]. Clinical presentation depends on the timing and progression of thrombosis and collateral formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a phenomenon to help keep liver to retain its functioning in a normal way; however, if this cavernous formation is unable to handle mesenteric and splenic inflow, the formation of pre-sinusoidal portal hypertension or cirrhosis ensues. Obstruction of portal veins was first diagnosed in 1869 by Stewart and Balfour in a patient with variceal dilation, enlarged spleen and ascites [4]. Clinical presentation depends on the timing and progression of thrombosis and collateral formation.…”
Section: Discussionmentioning
confidence: 99%
“…It may reveal abnormal growth of portal venous channels and can be supplemented with color Doppler which has 90% sensitivity of PVT diagnosis [4]. The diagnosis may also be confirmed by performing a CT scan and/or MRI with greater anatomical details.…”
Section: Discussionmentioning
confidence: 99%
“…CTPV occurs in patients with PVT due to the obstruction to the flow of portal blood leading to the development and dilation of multiple small vessels in and around the recanalising main portal vein. The cause of CTPV is not known, but it can occur in healthy livers with chronic non-cirrhotic and non-tumoural PVT 21 22. Third, small siderotic nodules of the spleen, called γ-Gandy bodies, have been seen on MRI in patients with portal vein or splenic vein thrombosis 23.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos et al 2 reported a case of a 58-year-old man with cavernous transformation of the portal vein secondary to PVT who presented with anaemia, electrolyte imbalance and deranged LFTs. In this case, no intervention was offered as the patient was considered a poor candidate for an invasive procedure and the LFTs improved spontaneously.…”
Section: Discussionmentioning
confidence: 99%